INTERVENSI ILMI-SPARE DALAM MENURUNKAN STATUS DEPRESI PADA KELOMPOK LANSIA - Ani Auli Ilmi (Universitas Islam Negeri Alauddin Makassar, 2017)
One of nursing community intervention to decrease depression level of elderly is ILMI SpaRe. The aim of this report is to show description application of ILMI SpaRe intervention for erlderly with depression in community nursing care. Result shows decreasing level of depression in older people for knowledge by 10,08%, attitude by 8,05 % and 60,8% for skill in spiritual care intervention and progressive muscle relaxation. By result of intervention application of ILMI SpaRe is concluded that spiritual care intervention combined with progressive muscle relaxation can reduce depression in older people group. This research is recommended for decision maker elderly program in community to increase community empowerment, activation self help group for elderly with health problem, especially depression and involving the seniors in community activities as form for appreciations, so older people can live health and healthy